Degradation of chloramphenicol by Ti/PbO2–La anodes and alteration in bacterial community and antibiotics resistance genes. (15th May 2022) - Dong, Hao; Fu, Yanli; Wang, Pengqi; Jiang, Wenqiang; Gao, Guangfei; Zhang, Xuan
Abstract: Antibiotics accumulation in the environment has given rise to multi-drug resistant 'superbugs' and antibiotics resistence genes (ARGs). Chloramphenicol (CAP), a kind of widely used antibiotics, was chosen as the model compound to investigate its degradation during electrochemical treatment process. The prepared Ti/PbO2 –La electrodes had a denser surface and a more complete PbO2 crystal structure than Ti/PbO2 electrode. The doping of La increased the onset potential and the overpotential, increased the current value of the oxidation peak and the reduction peak, reduced the impedance, and increased the lifetime. The reactions CAP degradation and TOC removal on Ti/PbO2 –La electrode was both primary kinetic reactions. CAP degradation rate increased with current density, and TOC obtained the highest removal at current density of 25 mA cm −2 . The electrolyte concentration had a small effect in the range of 0.050–0.150 mol L −1 . The effects under acidic and neutral conditions were better than under alkaline conditions. CAP was mainly directly oxidized at the electrode surface and indirect oxidation also took place via generated ·OH and SO4 ·- . 15 intermediates and 2 degradation pathways have been postulated. The entry of CAP and CAP intermediates into the environment caused the alteration in bacterial community and ARGs, while complete degradation products had little effect on them. Redundancy analysis showed that intI1 was the dominant factor affecting ARGs, and Actinobacteria and Patescibacteria were the main factors affecting the abundances of ARGs in the microbial community. Graphical abstract: Image 1 Highlights: The doping of La optimized the crystal structure of PbO2 crystals. The Ti/PbO2 –La anode showed superb stability and catalytic activity. 2 degradation pathways of CAP were postulated and 15 intermediates were identified. The effects of intermediates and complete products on ARBs and ARGs were different.